Luigi Ceriani, 1912-1999 - RONCAGLIA, A. (PSL Quarterly Review, 2013)
Luigi Ceriani (1912-1999) was the founder of Moneta e Credito and Banca Nazionale del Lavoro Quarterly Review, and their editor for the first forty years of their lives. The article illustrates his life history, in particular his role in the founding and in the successive life of the two journals as well as in the Banca Nazionale del Lavoro as director of its Economic Research Department. JEL Codes: A11